The association study between mri and percutaneous transpedicular biopsy (hpe) findings in vertebral lesions - Sidik, Che Kob (2008)
Magnetic resonance imaging (MRI) has become the instrument of choice for disease detection in spine pathology. More recent report have questioned the specificity of MRI detection and concluded that signal intensity change alone is not diagnostic of metastatic lesion. The introduction of percutaneous biopsy has substantially benefited the diagnosis of skeletal disease. It avoids the need for open surgical biopsy in most patients. Percutaneous transpedicular biopsy for vertebral lesions can be performed with minimal morbidity and good diagnostic yield with accuracy up to 92% in bone metastases (Ryohei Ashizawa et al, 1999). Our main objective is to determine the sensitivity and specificity of MRI in disease detection for vertebral spinal lesion specifically in vertebral tuberculosis and metastases. The association between MRI findings were made with transpedicular biopsy findings (histopathological diagnosis). The secondary objective was to determine the correlation of transpedicular biopsy done under Carm fluoroscopy with respect to major influencing variables such as spinal level, tissue type (lytic and sclerotic) and ultimate tissue pathologic diagnosis (HPE). In this retrospective study case series, we reviewed 72 patients admitted to our orthopaedic department in Hospital Kuala Lumpur and Hospital University Science, Malaysia between January 2002 to December 2007. All patients with suspected case of metastases, tuberculosis and pyogenic disease based on their clinical sign, symptoms and Xray findings involving spinal vertebra who underwent MRI and percutaneous transpedicular biopsy were included in the study. The data collected were reviewed and all data pertaining to laboratory investigations i.e FBC (full blood count), ESR (erythrocyte sedimentation rate), tumor marker, Sputum AFB (acid fast bacilli), Mantoux test and PCR (polymerase chain reaction) to assist in disease confirmation were taken to support for clinical diagnosis. The MRI findings of each cases reported by radiologist were reviewed to get radiological diagnosis. The HPE result from the tissues taken through percutaneous transpedicular biopsies procedure which were performed later to MRI to obtain histopathological diagnosis for final disease confirmation were reviewed. The data obtained were analysed for association. The overall HPE diagnosis obtained for disease detection through transpedicular biopsy were 65% positive (forty seven of seventy two) and negative 34.5% (twenty five of seventy two) for both vertebral tubeculosis and metastases. The overall disease detection by MRI were 97.2% (seventy of seventy two ). There was no significant association between MRI findings with percutaneous transpedicular biopsy (HPE) (p value >0.05) for disease detection. From overall study population, the prevalence of disease detected by percutaneous transpedicular biopsy was 0.653 ( 95%CI 0.543, 0.763 ) and the prevalence of similar disease detected by MRI was 0.972 ( 95% Cl 0.934,1.011 ). The sensitivity and specificity of magnetic resonance imaging (MRI) to detect the disease compared to percutaneous transpedicular biopsy which was taken as gold standard in this study were 0.979 (95% Cl 0.937, 1.020) and 0.040 (95% Cl 0.018, 0.062) respectively. With respect to vertebral level, there was significant association between level of vertebra lesion involved with HPE diagnosis in percutaneous transpedicular biopsy procedure (p value 0.021 ). For tissue type, there was no significant association between tissue type in vertebral body lesion with HPE obtained through transpedicular biopsy procedure (p value 0.256).Based on this study, we can conclude that MRI is highly sensitive for disease detection in vertebral lesion. The MRI however has low specificity and not reliable in detecting true negative disease. There is no significant association between MRI and transpedicular biopsy method for disease detection. For inconclusive MRI findings, transpedicular biopsy is clinically useful and reliable to confirm the vertebral disease. For obvious MRI finding with vertebral metastases and tuberculosis, transpedicular biopsy is reliable for confirmation disease diagnosis.